2019
DOI: 10.2345/0899-8205-53.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Automated, Web-Based Solution for Bidirectional EHR–Infusion Pump Communication

Abstract: Smart Agent is a web-based solution for establishing bidirectional communication between an infusion pump and an electronic health record (EHR). It eliminates the need for clinician double check of medication administration using an infusion pump. Because the clinician already is using the EHR to review patient health information and update status, the addition of the web service would help eliminate the potential for human error when using a manual system. The Smart Agent process encompasses the reading of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, several technical improvements, in terms of device-equipped smart functions and linkage on the electronic medical record (EMR) server, have been made to promptly detect erroneous device settings. 914 However, although such previous research demonstrated improvements in patient safety, several obstacles can prevent hospitals from adopting such devices. First, the price of a smart infusion pump is generally two- or three-times higher than that of conventional non-smart devices; therefore, the financial burden of purchasing sufficient smart infusion pumps can be a barrier for most hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several technical improvements, in terms of device-equipped smart functions and linkage on the electronic medical record (EMR) server, have been made to promptly detect erroneous device settings. 914 However, although such previous research demonstrated improvements in patient safety, several obstacles can prevent hospitals from adopting such devices. First, the price of a smart infusion pump is generally two- or three-times higher than that of conventional non-smart devices; therefore, the financial burden of purchasing sufficient smart infusion pumps can be a barrier for most hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Technical and clinical process details of the SA system have been previously published. 12 13 The online supplemental appendix includes full information for each scenario. The order of scenarios remained constant across participants.…”
Section: Methodsmentioning
confidence: 99%
“…The SA was developed using a systems engineering approach. 12 We sought to explore the degree to which the SA system could improve safety and efficiency of insulin infusion practices.…”
Section: Introductionmentioning
confidence: 99%
“…8 The integration of infusion pumps to the EHR presents significant technical challenges that require an established infrastructure, technical resources, and appropriate commitment to the project at the level of the healthcare system. [9][10][11] These systems integrate clinical provider order entry (CPOE)-based infusion orders with IV infusion pump devices. Interoperable infusion pump workflows between pump and EHR can reduce the number of steps by over 50%, primarily by conducting pump programming and EHR documentation for the clinician.…”
Section: Introductionmentioning
confidence: 99%